Irrigação com água salobra e ambiência agrícola no desempenho agronômico da cultura do tomate - Goes, Geovana Ferreira (2023)
The objective of the research was to evaluate the agronomic performance of tomato hybrids irrigated with brackish water under different growing environments. The research was carried out from July to October 2022, at Sítio Flexeiras, belonging to the municipality of Aratuba, located in the Maciço de Baturité region, Ceará. The experimental design used was randomized blocks, in a sub-subdivided plot, with five replications. The plots consisted of two cultivation environments (A1= protected environment and A2= full sun), the subplot of five water electrical conductivity (ECa) (1.0; 1.7; 2.4; 3.1 and 3 .8 dS m-1) and the sub-subplot of two hybrids (Itaipava and BS DI0014). The following variables were evaluated: Number of leaves, plant height, stem diameter, leaf area, net photosynthetic rate, leaf temperature, transpiration rate, stomatal conductance, transpiration, internal CO2 concentration, temperature, water use efficiency , number of commercial, non-commercial and total fruits, average mass of commercial, non-commercial and total fruits, productivity of commercial, non-commercial and total fruits, soluble solids content, hydrogen potential, length and diameter of the fruit, number of locules and pulp thickness. The Itaipava hybrid grown in a protected environment shows greater tolerance to saline stress in terms of plant height, number of leaves and leaf area, while the stem diameter was greater under protected environmental conditions. Saline stress reduced photosynthetic rates more intensely in the full sun environment, while the use of lower salinity water in the protected environment provides greater stomatal conductance. The hybrid BS DI0014 was more tolerant to saline stress in terms of transpiration in the protected environment and in full sun. The Itaipava and BS DI0014 hybrids grown in a protected environment have a higher internal concentration of CO2. Saline stress negatively affected the productivity of non-commercial and total fruits, but with less intensity in the protected environment. Cultivation of the Itaipava hybrid in a full sun environment was more tolerant to salts, while BS DI0014 was grown in a protected environment for non-commercial fruits. The increase in the electrical conductivity of irrigation water reduces the productivity of commercial fruits. The Itaipava hybrid presents greater productive performance of commercial and total tomato fruits. Cultivation of tomato plants in a protected environment promotes greater fruit length and diameter values for the Itaipava hybrid in tomato cultivation. Salinity favors an increase in the content of soluble solids in tomato fruits, but with greater intensity in the protected environment.